THE STUDY OF SINGLE AND DOUBLE INTEGRATION FORMULA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
We introduce a new double transform called double Elzaki transform (modification of Smudu transform), where we will study this transform and their theorems on convergence. Also, we discuss the double new transform and it is convergent. Recently, Brychkov evaluated some new classes of definite and indefinite single and double integrals involving various elementary special functions and the logarithmic function. Single Integral is the building block of double and triple integrals, so if you are not able to do single integrals, you cannot do double and triple integrals. In calculus, and more generally in mathematical analysis, integration by parts or partial integration is a process that finds the integral of a product of functions in terms of the integral of the product of their derivative and antiderivative. In a very interesting, useful and popular research paper, Brychkov evaluated several integrals (single and double) of these types and gave several interesting special cases.